The therapeutic potential of polyunsaturated fatty acids in the management of inflammatory skin disorders - Wójcik, Emilia; Korczak, Anna; Łopacińska, Olga; Szewczyk, Oliwia; Czarnecka, Karolina; Burda, Katarzyna; Korn, Aleksandra; Olek, Ewa; Stańczyk, Katarzyna; Jędrzejczyk, Justyna (Quality in Sport, 2024)
Introduction and purpose: Polyunsaturated fatty acids (PUFAs) are a well-known component of a nutritionally balanced diet. There is a wealth of evidence demonstrating that the ingestion of these substances enhances health, as they are involved in a multitude of metabolic processes that are essential for cellular functionality. However, the contemporary Western diet is distinguished by a reduction in the consumption of omega-3 polyunsaturated fatty acids (PUFAs). The objective of this review is to present the potential therapeutic efficacy of omega-3 PUFA supplementation in the most common inflammatory skin disorders, such as acne vulgaris, atopic dermatitis and psoriasis vulgaris. State of knowledge: Acne vulgaris, atopic dermatitis and psoriasis vulgaris differ in terms of their pathophysiology. However, they are all characterised by underlying inflammatory processes. Omega-3 fatty acids have been demonstrated to possess anti-inflammatory properties. They are capable of modulating both the innate and the adaptive immune responses, thereby alleviating the symptoms of the aforementioned skin disorders. Summary: Given the pluripotent anti-inflammatory qualities of omega-3 polyunsaturated fatty acids, it is reasonable to conclude that they have the potential to become an effective therapeutic tool in the management of inflammatory skin diseases.